Barriers to participation in clinical trials: cross-sectional study on perceptions of oncology patient advocacy group webpage in Brazil - Julian, Guilherme Silva; Bueno, Christiane; Martins, Renata Eiras; de-Barros, Luciana Holz Camargo (Brazilian Journal of Oncology, 2019)
Introduction: Clinical trials (CT) represent an important alternative treatment for oncologic patients. Also, CTs represent an essential step to development of improved therapeutic strategies. However, little is known on Brazilian perception regarding CT. The aim of this survey was to describe the overall perception of CT in Brazilian participants of oncology patient advocacy group. Design and setting: Cross-sectional survey conducted online through patient advocacy group website. Methods: From April 2012 to October 2014, 254 respondents answered an internet-based survey related to knowledge on CT from an independent nonprofit oncology patient advocacy group. Results: Overall, about 85% of respondents stated they would participate in an oncology trial. Of all respondents, 99.9% believe that CTs can contribute positively to advancement of cancer treatment by increasing the scientific knowledge, improving the treatment, finding a cure, providing a new treatment option, or improving the quality of life. Also, 96% affirmed they have already had some information on CT, being internet the most used form of communication (69%), followed by physicians orientation (8%), magazines and newspaper (8%), and hospital handout material (7%). In addition, only 18 respondents reported previously participation in CTs (6.9%), and approximately 10% answered they knew someone that participated in a CT (e.g. friend or other). Conclusions: This survey demonstrated that respondents associate CT as an option in cancer treatment; however, only a small number of respondents have participated in a CT previously. The data indicate the lack of available information as the current major barrier to CT participation in Brazil.
Keywords: Clinical trial; Patient advocacy; Awareness; Physician-Patient relations; Health surveys.